Android Based Student Feedback System for Improved Teaching Learning - Shinde, AB; Karade, V.L; Sutar, SS (International Journal of Computer Sciences and Engineering, 2019)
The process used to collect the student’s feedback is manual and takes more time to complete its analysis and report generation. As technology is changing at fast rate, maximum numbers of android application are available for educational purpose. In recent years the android technology with web services has brought many drastic changes in the mobile application development field. In this paper we proposed a system which provides a simple interface for collection and analysis of student’s feedback. It can be used by educational institutes or colleges to maintain the records of student’s feedback. Valuing and asking for feedback has recognized benefits for both faculty and students. For faculty to develop and improve teaching skills. Using this application, students can fill their feedback through any android based mobile. Once they submit it, their feedback will be analyzed quickly and feedback report can be generated within very short span of time.